SGLT2 inhibitors for the prevention of kidney failure in patients with type 2 diabetes: a systematic review and meta-analysis. Issue 11 (November 2019) - Neuen, Brendon L; Young, Tamara; Heerspink, Hiddo J L; Neal, Bruce; Perkovic, Vlado; Billot, Laurent; Mahaffey, Kenneth W; Charytan, David M; Wheeler, David C; Arnott, Clare; Bompoint, Severine; Levin, Adeera; et al.
Summary: Background: The effects of sodium-glucose co-transporter-2 (SGLT2) inhibitors on kidney failure, particularly the need for dialysis or transplantation or death due to kidney disease, is uncertain. Additionally, previous studies have been underpowered to robustly assess heterogeneity of effects on kidney outcomes by different levels of estimated glomerular filtration rate (eGFR) and albuminuria. We aimed to do a systematic review and meta-analysis to assess the effects of SGLT2 inhibitors on major kidney outcomes in patients with type 2 diabetes and to determine the consistency of effect size across trials and different levels of eGFR and albuminuria. Methods: We did a systematic review and meta-analysis of randomised, controlled, cardiovascular or kidney outcome trials of SGLT2 inhibitors that reported effects on major kidney outcomes in people with type 2 diabetes. We searched MEDLINE and Embase from database inception to June 14, 2019, to identify eligible trials. The primary outcome was a composite of dialysis, transplantation, or death due to kidney disease. We used random-effects models to obtain summary relative risks (RRs) with 95% CIs and random-effects meta-regression to explore effect modification by subgroups of baseline eGFR, albuminuria, and use of renin–angiotensin system (RAS) blockade. This review is registered with PROSPERO (CRD42019131774). Findings: From 2085 records identified, four studies met our inclusion criteria, assessing three SGLT2 inhibitors: empagliflozin (EMPA-REG OUTCOME), canagliflozin (CANVAS Program and CREDENCE), and dapagliflozin (DECLARE–TIMI 58). From a total of 38 723 participants, 252 required dialysis or transplantation or died of kidney disease, 335 developed end-stage kidney disease, and 943 had acute kidney injury. SGLT2 inhibitors substantially reduced the risk of dialysis, transplantation, or death due to kidney disease (RR 0·67, 95% CI 0·52–0·86, p=0·0019), an effect consistent across studies ( I 2 =0%, pheterogeneity =0·53). SGLT2 inhibitors also reduced end-stage kidney disease (0·65, 0·53–0·81, p<0·0001), and acute kidney injury (0·75, 0·66–0·85, p<0·0001), with consistent benefits across studies. Although we identified some evidence that the proportional effect of SGLT2 inhibitors might attenuate with declining kidney function (ptrend =0·073), there was clear, separate evidence of benefit for all eGFR subgroups, including for participants with a baseline eGFR 30–45 mL/min per 1·73 m 2 (RR 0·70, 95% CI 0·54–0·91, p=0·0080). Renoprotection was also consistent across studies irrespective of baseline albuminuria (ptrend =0·66) and use of RAS blockade (pheterogeneity =0·31). Interpretation: SGLT2 inhibitors reduced the risk of dialysis, transplantation, or death due to kidney disease in individuals with type 2 diabetes and provided protection against acute kidney injury. These data provide substantive evidence supporting the use of SGLT2 inhibitors to prevent major kidney outcomes in people with type 2 diabetes. Funding: None.